Application of Fiber Made from Bark of Salak (Salacca Zalacca) Tree as Reinforcement in Polymer Matrix Composites - Laksono, Andromeda Dwi; Tajalla, Gusti Umindya; Parusha, Oliever Andrea (International Journal of Mechanical Engineering Technologies and Applications, 2021)
Although Indonesia is abundant supply of salak (Salacca zalacca) fruit, bark of salak is not yet advanced utilized. This work therefore chracterized its fiber and process it into polymer matrix composites. The study was conducted using varied chemical treatments. Delignification using NaOH solution with concentration of 1%, 5%, 10% with 3 hours immersion time. Bleaching treatment was using H2O2 media with varied immersion time at 30, 60 and 90 minutes. Tensile tests, impact tests, microscopic image test using scanning electron microscopy (SEM) and chemical composition test using fourier-transform infra-red (FTIR) spectroscopy were carried out in this work. This work showed that optimal delignification treatment can be found when 5% NaOH concentration was used. The corresponding ultimate tensile strength and impact strength were 25.47 MPa and 11.95 kJ/m2, respectively. The optimal bleaching treatment was 90 minutes immersion. The results of SEM image analysis showed that the salak midrib fiber composite without treatment has a lousy interface. Meanwhile, fiber with delignification treatment only has reasonable good interface and fiber with delignation treatment followed by bleaching treatment has excellent interface. FTIR test results showed that the salak midrib fiber composite without treatment had a cellulose component although hemicellulose and lignin levels still dominated. The delignification treatment had succesfully broken the lignin-specific C = O bond but still could not eliminated hemicellulose and lignin bond. In comparison, bleaching treatment reduced intensity of OH intensity, CH and CO which are typical hemicellulose and lignin functional groups. Based on the results of the study, salak midrib fiber with delignification chemical treatment using 5% NaOH for 3 hours followed by bleaching treatment using 2% H2O2 for 90 minutes was the best treatment.